Mycobacterium avium Subsp. avium and Subsp. hominissuis Give Different Cytokine Responses after in vitro Stimulation of Human Blood Mononuclear Cells - Thegerström, Johanna; Jönsson, Bodil; Brudin, Lars; Olsen, Björn; Wold, Agnes E.; Ernerudh, Jan; Friman, Vanda (PLOS ONE, 2012)
Background Mycobacterium avium is the principal etiologic agent of non-tuberculous lymphadenitis in children. It is also a known pathogen for birds and other animals. Genetic typing of M. avium isolates has led to a proposal to expand the set of subspecies to include M. avium subsp. hominissuis. Isolates associated with disease in humans belong to this subspecies. Methodology/Principal Findings Peripheral blood mononuclear cells from six healthy blood donors were stimulated in vitro with ten isolates of M. avium avium and 11 isolates of M. avium hominissuis followed by multiplex bead array quantification of cytokines in supernatants. M. avium hominissuis isolates induced significantly more IL-10 and significantly less IL-12p70, TNF, IFN-γ and IL-17 when compared to M. avium avium isolates. All strains induced high levels of IL-17, but had very low levels of IL-12p70. Conclusion/Significance The strong association between M. avium subsp. hominissuis and disease in humans and the clear differences in the human immune response to M. avium subsp. hominissuis compared to M. avium subsp. avium isolates, as demonstrated in this study, suggest that genetic differences between M. avium isolates play an important role in the pathogenicity in humans.